2010
DOI: 10.1292/jvms.09-0524
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Toltrazuril and Its Metabolites, Toltrazuril Sulfoxide and Toltrazuril Sufone, after a Single Oray Administration to P1gs

Abstract: ABSTRACT. Toltrazuril (TZR) is a triazine-based antiprotozoal agent. Following a single oral administration of TZR at 10 and 20 mg/kg to male pigs, the mean TZR concentration in plasma peaked at 4.24 and 8.18 g/ml at 15.0 and 12.0 hr post-dose, respectively. TZR absorbed was rapidly converted to the short-lived intermediary metabolite toltrazuril sulfoxide (TZR-SO), and then metabolized to the reactive toltrazuril sulfone (TZR-SO 2 ). TZR-SO 2 was actually more slowly eliminated, with average half-lives of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 12 publications
3
23
2
Order By: Relevance
“…The apparent terminal elimination half-lives of TZR in broilers were 12.1 and 13.0 h after oral administration of 10 or 20 mg/kg of TZR, respectively. However, the half-life of TZR from our study was shorter than that in rats (23.0 h for 20 mg/kg, EMEA, 1998), rabbits (52.7 h for 10 mg/kg, 56.7 h for 20 mg/kg, Kim et al, 2010), pigs (48.7 h for 10 mg/kg, 68.9 h for 20 mg/kg, Lim et al, 2010), horses (55 h for 10 mg/kg, Tobin et al, 1997; 61.4 h for 10 mg/kg, Furr and Kennedy, 2000) and calves (154.0 h for 15 mg/kg, EMEA, 2004). These clearly indicate speciesspecific differences in terms of absorption and elimination characteristics of TZR following oral dosing.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…The apparent terminal elimination half-lives of TZR in broilers were 12.1 and 13.0 h after oral administration of 10 or 20 mg/kg of TZR, respectively. However, the half-life of TZR from our study was shorter than that in rats (23.0 h for 20 mg/kg, EMEA, 1998), rabbits (52.7 h for 10 mg/kg, 56.7 h for 20 mg/kg, Kim et al, 2010), pigs (48.7 h for 10 mg/kg, 68.9 h for 20 mg/kg, Lim et al, 2010), horses (55 h for 10 mg/kg, Tobin et al, 1997; 61.4 h for 10 mg/kg, Furr and Kennedy, 2000) and calves (154.0 h for 15 mg/kg, EMEA, 2004). These clearly indicate speciesspecific differences in terms of absorption and elimination characteristics of TZR following oral dosing.…”
Section: Resultscontrasting
confidence: 57%
“…Maximum plasma concentration of TZR-SO was observed very early, suggesting the conversion of the parent drug to TZR-SO was very rapid following oral administration of TZR. After oral administration of 10 mg/kg of TZR, elimination half-lives of TZR-SO in broiler was 14.7 h, much shorter than in rabbits (56.1 h, 10 mg/kg of TZR, Kim et al, 2010) and pigs (51.9 h, 10 mg/kg of TZR, Lim et al, 2010). The average plasma elimination half-life of TZR-SO 2 in broilers has been reported to be around 80.3 h after oral administration of TZR (10 mg/kg), being similar to that observed in rabbits .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are limited published pharmacokinetic data evaluating toltrazuril. Following oral administration of 10 mg/kg in pigs, toltrazuril is well absorbed, reaching maximum concentrations ~15 hr postadministration (Lim et al., ). In rabbits, toltrazuril is well absorbed following oral administration, resulting in a prolonged elimination half‐life ( T 1/2 ) of 20 hr and achieving concentrations associated with other reports of clinical efficacy (Hu, Liu, Shang, Yang, & Yang, ).…”
Section: Pharmacokinetics Of Triazinesmentioning
confidence: 99%
“…In this study the levels in the blood showed a steady decline and had reduced to about half this C max value by 6 days. Toltrazuril has also been shown to have a relatively slow elimination rate in pigs (Lim et al, 2010), llamas (Prado et al, 2011) and horses (Dirikolu et al, 2009a). To date there are no published pharmacological studies in sheep.…”
Section: Discussionmentioning
confidence: 99%